2018
DOI: 10.1534/genetics.118.300822
|View full text |Cite
|
Sign up to set email alerts
|

Bimodal Expression of theSalmonellaTyphimuriumspvOperon

Abstract: The well-studied spv operon of Salmonella typhimurium is important for causing full virulence in mice and both the regulation and function of the Spv proteins have been characterized extensively over the past several decades. Using quantitative single-cell fluorescence microscopy, we demonstrate the spv regulon to display a bimodal expression pattern that originates in the bimodal expression of the SpvR activator. The spv expression pattern is influenced by growth conditions and the specific S. typhimurium str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 83 publications
1
19
0
Order By: Relevance
“…The pathogenic factors of Salmonella include endotoxin, enterotoxin, and virulent effectors encoded by bacterial genetic elements. Most pathogenic Salmonella harbor a pSLT virulence plasmid of around 90 kb that contains a highly conserved 8-kb region of five genes (spvRABCD), which have been reported to be implicated in intracellular survival and growth (Guiney and Fierer, 2011;Passaris et al, 2018). Previously, we showed that Salmonella spvB gene could reduce host cell autophagy and regulate intracellular iron homeostasis (Chu et al, 2016;Yang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The pathogenic factors of Salmonella include endotoxin, enterotoxin, and virulent effectors encoded by bacterial genetic elements. Most pathogenic Salmonella harbor a pSLT virulence plasmid of around 90 kb that contains a highly conserved 8-kb region of five genes (spvRABCD), which have been reported to be implicated in intracellular survival and growth (Guiney and Fierer, 2011;Passaris et al, 2018). Previously, we showed that Salmonella spvB gene could reduce host cell autophagy and regulate intracellular iron homeostasis (Chu et al, 2016;Yang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…2, LacZ activity and fluorescence stemming from the lacZ::Tn5-PLtetO-1-msfGFP::lacZ construct could indeed be induced with aTc but not with IPTG. In turn, after flipping out the the tetR-kan-PLtetO-1 cassette by recombination of the frt sites, the resulting lacZ::msfGFP::lacZ in-frame "sandwhich" construct (similar to those obtained with other transposons(Gregory et al, 2010;Passaris et al, 2018)) could be confirmed with sequencing, and yielded LacZ activity and fluorescence after induction with IPTG instead of aTc.…”
mentioning
confidence: 81%
“…Together with the advent of monomeric, fast-folding and bright fluorescent proteins with different spectral properties, this approach has allowed the accurate monitoring of dynamic expression and localization patterns of proteins and protein complexes in both prokaryotic and eukaryotic organisms (Breker et al, 2013;Kuwada et al, 2014;Chong et al, 2015). However, while for a few well-studied model organisms ordered libraries have been made (Kitagawa et al, 2006;Werner et al, 2009;Taniguchi et al, 2010;Breker et al, 2013), the tools for genome-wide screening of potentially interesting protein localizations are still limited (Gregory et al, 2010;Passaris et al, 2014;Passaris et al, 2018). Especially when trying to study proteins as they are (sometimes lowly) expressed from their native chromosomal locus.…”
Section: Introductionmentioning
confidence: 99%
“…Salmonella plasmid virulence ( spv ) gene, a highly conserved 8-kb region in the pSLT virulence plasmid from non-typhoid Salmonella strains of clinically significant serovars, has been implicated in intracellular survival and growth ( Fabrega and Vila, 2013 ). The spv region contains a positive transcriptional regulator gene spvR , a negative regulator gene spvA , and three structural genes spvB , spvC , and spvD ( Guiney and Fierer, 2011 ; Passaris et al., 2018 ). Previous studies have found that all the spv effectors are secreted via the T3SS, and spv -containing Salmonella exhibit enhanced intracellular proliferation in intestinal and extraintestinal tissues of the natural host ( Libby et al., 1997 ), suggesting that they have the potential to target molecules and mechanisms to attenuate host inflammatory response to establish a successful infection.…”
Section: Introductionmentioning
confidence: 99%